Philosophy of Science Perspective on Farmer Behavior in Adopting Coffee Post-Harvest Technology to Support Sustainable Agriculture - MURAD, Murad; Sarjan , Muhammad; Anwar, Hairil; Sumarsono, Joko (Journal of Multidisciplinary Science and Natural Resource Management, 2025)
Sustainable agriculture has emerged as a critical solution to address global challenges such as climate change, land degradation, and increasing food demand. In the context of coffee commodities, post-harvest processes play a vital role in determining product quality and economic value. However, the adoption of post-harvest technologies by farmers is often hindered by non-technical factors, including local knowledge, cultural values, and philosophical beliefs. This article aims to analyze farmers' behavior in adopting post-harvest coffee technologies through the lens of the philosophy of science. Using the approaches of epistemology, ontology, and axiology, this study explores how the construction of knowledge, social reality, and ethical values influence farmers' decisions. Data were collected through in-depth interviews with 30 coffee farmers in Bandung Regency, West Java, and six months of participatory observation. The results reveal that traditional knowledge remains dominant compared to scientific knowledge, while social realities and cultural values significantly shape farmers' behavior. This article provides new insights for policymakers and agricultural extension workers to design more inclusive and locally contextualized strategies to support sustainable agriculture. The study also underscores the importance of integrating the philosophy of science perspectives into farmer behavior analysis to understand the complexities of technology adoption.